Brazilian Hydropolitics under the United Nations 2030 Agenda - Battistello Espindola, Isabela (2020)
The global framework set forth by the United Nations 2030 Agenda and its Sustainable Development Goals (SDG) include water resources in their scope, which emphasizes how water assets and society well-being are closely intertwined and how crucial they are to achieving sustainable development. This paper explores the role of hydropolitics in that Post-2015 Development Agenda and uses Brazilian hydropolitics set to reach SDG6 as a case study.